2015
DOI: 10.1002/cam4.509
|View full text |Cite
|
Sign up to set email alerts
|

The relationships among individual and regional smoking, socioeconomic status, and oral and pharyngeal cancer survival: a mediation analysis

Abstract: Poorer survival from oral and pharyngeal cancer (OPC) has been reported for populations of lower socioeconomic status (SES), adjusting for risk factors such as patient and clinical characteristics. Beyond these risk factors, higher rates of tobacco use may be a mediator for the observed poorer OPC survival for low SES populations. In this study, we aimed to examine the impact of the relationships among SES, individual smoking status, and living in a region with a higher smoking rate on OPC survival. We obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 24 publications
3
38
0
Order By: Relevance
“…We observed that patients in the smallest, most highly subsidized apartments had the worst survival, even after adjusting for age, sex, smoker status, and stage at presentation, an effect that was not explained by delayed disease presentation. This is similar to findings with regard to socioeconomic status and HNSCC survival in other contexts . It is worth noting that we did not observe any significant racial differences in our multivariable analysis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We observed that patients in the smallest, most highly subsidized apartments had the worst survival, even after adjusting for age, sex, smoker status, and stage at presentation, an effect that was not explained by delayed disease presentation. This is similar to findings with regard to socioeconomic status and HNSCC survival in other contexts . It is worth noting that we did not observe any significant racial differences in our multivariable analysis.…”
Section: Discussionsupporting
confidence: 90%
“…Socioeconomic status affects the survival of patients diagnosed with head and neck squamous cell carcinoma (HNSCC) . Incidence rates for this cancer are higher in developing countries compared with developed nations and for patients of lower socioeconomic status, even in health systems with universal health care in developed countries .…”
Section: Introductionmentioning
confidence: 99%
“…Next, we did not take into consider socio-economic status (SES). A number of studies have proven the value of SES in HNSCC [29][30][31]. Hence, we recommend that future studies should investigate whether SES might be value prediction to survival outcome in LSCC, and evaluate the additional worth of this factor in a multivariable prediction model.…”
Section: Discussionmentioning
confidence: 99%
“…10 Among all parameters that represent health-care disparities, socioeconomic status (SES) is a major determinant of economic resources and has been shown to greatly impact health outcomes. 1,11 Hematopoietic cell transplantation (HCT) is a complex, highly-specialized and resource-intensive procedure that is available at selected centers in the country, and hence may be especially prone to health-care disparities. 12 The association of sociodemographic factors with access and outcomes has been reported in allogeneic HCT; 12,13 African-Americans are less likely to receive allogeneic HCT for leukemia and lymphoma.…”
Section: Introductionmentioning
confidence: 99%